2017
DOI: 10.23960/jat.v5i2.1834
|View full text |Cite
|
Sign up to set email alerts
|

EFEKTIVITAS Pseudomonas fluorescens DAN Paenibacillus polymyxa TERHADAP KEPARAHAN PENYAKIT KARAT DAN HAWAR DAUN SERTA PERTUMBUHAN TANAMAN JAGUNG MANIS (Zea mays var. saccharata)

Abstract: Penyakit penting pada tanaman jagung diantaranya adalah penyakit karat daun yang disebabkan oleh jamur Puccinia sorghi Schwein dan penyakit hawar daun yang disebabkan oleh jamur Helmithosporium turcicum Leonard et Suggs. Penelitian ini bertujuan untuk menguji keefektifan Pseudomonas fluorescens dan Paenibacillus polymyxa dalam menekan perkembangan penyakit karat dan hawar daun jagung serta memicu pertumbuhan tanaman jagung. Penelitian ini dilakukan pada bulan September sampai bulan Desember 2015 di Laboratoriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
1
0
3
Order By: Relevance
“…The result showed that the leaf rust disease intensity was developed continually in all varieties (Figure 1). This is in line with the results of research by Prasetyo et al [12] that the development of the severity of corn leaf rust disease shows an increase in each week of observation. The result of Suriani et al [24] indicated that there were some variations on rust severity development on every accession, and increment rust severity at everytime of observation at 50, 60, 70 DAP.…”
Section: Leaf Rust Disease Intensitysupporting
confidence: 92%
See 1 more Smart Citation
“…The result showed that the leaf rust disease intensity was developed continually in all varieties (Figure 1). This is in line with the results of research by Prasetyo et al [12] that the development of the severity of corn leaf rust disease shows an increase in each week of observation. The result of Suriani et al [24] indicated that there were some variations on rust severity development on every accession, and increment rust severity at everytime of observation at 50, 60, 70 DAP.…”
Section: Leaf Rust Disease Intensitysupporting
confidence: 92%
“…Leaf rust disease has early symptoms in the form of small yellow spots. The spots are scattered on the leaf surface which causes the leaves to dry out in case of further infection [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Apabila penyakit ini dibiarkan dan dalam kondisi cuaca yang mendukung patogennya untuk berkembang akan menyebabkan perkembangan dan penyebaran dari penyakit karat daun ini semakin meluas dan akhirnya daun jagung akan mengering bahkan mati (Talanca & Tenrirawe, 2015). Penyakit karat daun juga dapat menurunkan hasil produksi sebesar 70% (Prasetyo et al, 2017). Penyakit selanjutnya yaitu hawar daun.…”
Section: Insidensi Penyakit Hawar Daununclassified
“…Selain sebagai pangan pokok pada beberapa daerah di Indonesia seperti di Nusa Tenggara Timur (NTT), jagung juga dimanfaatkan untuk pakan ternak, tepung, minyak nabati dan bahan-bahan kosmetika (Mantau, 2016). (Crouch & Szabo, 2011;BBPOPT, 2022), yang selanjutnya menyebabkan matinya klorofil dan akhirnya menghambat produksi jagung (Prasetyo et al, 2017). Di Nusa Tenggara Timur serangan penyakit karat mencapai 40% (Dhena & Puu, 2011) atau bahkan 83.73% (Rusae et al, 2018).…”
Section: Pendahuluanunclassified